Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1468-2982.2002.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Headache and A Midbrain Vascular Malformation: Evidence for A Role of the Brainstem in Chronic Migraine

Abstract: Migraine is a common, disabling form of primary headache that has been linked by functional imaging studies to activation in the rostral brainstem. In specialty clinics migraine is most commonly seen in association with frequent less feature full headache that has been called transformed migraine or more recently termed chronic migraine. A patient is described with frequent migraine, 3 days per week, and less feature full headaches on other days. The patient has a cavernoma in the midbrain that has bled. She w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(92 citation statements)
references
References 46 publications
3
83
0
6
Order By: Relevance
“…2,3) Therefore, involvement of the dorsal lateral pons is thought to initiate migraine or migraine-like headache. 1,8,10,11) Interestingly, one case involved a lesion located in almost the same region as in the present case. Although our case could not be distinguished from cavernous hemangioma or AVM and only showed one episode of headache, the present case together with these other migraine cases indicate that dorsal pontine lesion can produce painful sensations restricted to the trigeminal nerve territory.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…2,3) Therefore, involvement of the dorsal lateral pons is thought to initiate migraine or migraine-like headache. 1,8,10,11) Interestingly, one case involved a lesion located in almost the same region as in the present case. Although our case could not be distinguished from cavernous hemangioma or AVM and only showed one episode of headache, the present case together with these other migraine cases indicate that dorsal pontine lesion can produce painful sensations restricted to the trigeminal nerve territory.…”
Section: Discussionsupporting
confidence: 59%
“…15,16) Migraine or migraine-like headache may develop following brainstem hemorrhage caused by cavernous hemangioma 1,10) and arteriovenous malformation (AVM). 8,11) Positron emission tomography studies have revealed that significant activation is seen in the brainstem, especially in the dorsal lateral pons, in patients with migraine without aura 13) and migraine triggered by 1,2-glyceryl trinitrate. 2,3) Therefore, involvement of the dorsal lateral pons is thought to initiate migraine or migraine-like headache.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a brainstem lesion in the area of PAG in a patient with CDH has been described [12]. The patient was found to have had a left-sided cavernoma in the dorsal midbrain region adjacent to the PAG.…”
Section: Midbrain Vascular Malformationmentioning
confidence: 95%
“…In a single case report a discrete sclerotic lesion in the region of the PAG in a patient with multiple sclerosis caused severe headache [5]. Recently, a brainstem lesion in the area of periaqueductal grey (PAG) in a patient with CDH has been described [6]. The patient had no previous history of headache and developed new daily persistent headache and on MRI a cavernous angioma was noted in the region of the PAG.…”
Section: Abstract Daily Headache • Functional Neuroimagingmentioning
confidence: 99%